Utility of “liquid biopsy” using pancreatic juice for early detection of pancreatic cancer - Okada, Tetsuhiro; Iwano, Hirotoshi; Ono, Yusuke; Karasaki, Hidenori; Sato, Takayuki; Yamada, Masataka; Omori, Yuko; Sato, Hiroki; Hayashi, Akihiro; Kawabata, Hidemasa; Goto, Takuma; Sasajima, Junpei; Takauji, Shuhei; Nagashima, Kazuo; Mizukami, Yusuke; Okumura, Toshikatsu (Endoscopy International Open, 2018)
Background Despite advances in the diagnosis of pancreatic ductal adenocarcinoma (PDA), histological evaluation of small and poorly defined masses in the pancreas is uncomfortable and unsafe.Methods We herein report a case of early stage PDA, in which multiple KRAS mutations were detected in the pancreatic juice preoperatively. A small hypoechoic area adjacent to the portal vein was detected through endoscopic ultrasound in the pancreatic body. KRAS mutations were evaluated using plasma, and the pancreatic juice by digital PCR.Results Pancreatic duct biopsy and pancreatic juice cytology were performed with no evidence of malignancy; however, KRAS mutations, KRAS G12V and G12D, were detected in the pancreatic juice. Histological assessment of the resected specimen demonstrated a solid tumor with desmoplastic reaction accompanied by carcinoma in situ in the main pancreatic duct where KRAS G12V mutation was identified. More detailed analysis demonstrated KRAS G12D mutation in the cluster of low grade pancreatic intraepithelial neoplasia, implying that the lesion developed independently.Conclusions Our study indicates the potential of “endoscopic liquid biopsy” to capture the driver gene for PDA diagnosis.